Vaccines Safety in Children and in General Population: A Pharmacovigilance Study on Adverse Events Following Anti-Infective Vaccination in Italy - Lombardi, Niccolò; Crescioli, Giada; Bettiol, Alessandra; Tuccori, Marco; Rossi, Marco; Bonaiuti, Roberto; Ravaldi, Claudia; Levi, Miriam; Mugelli, Alessandro; Ricci, Silvia; Lippi, Francesca; Azzari, Chiara; et al. (Frontiers in Pharmacology, 2019)
Background: The concern for adverse events following immunization (AEFI) and anti-vaccination movements that lacked scientific evidence-based supports may reduce vaccine uptake in the general population. Thus, the aims of the present study were to characterize AEFI in general population (all age groups), in terms of frequency, preventability, and seriousness and to define predictors of their seriousness in children. Methods: A retrospective study was performed on suspected AEFI reports for children and adults who received any form of vaccinations, collected in Tuscany, Italy, between 1 January and 31 December 2017. Patients’ characteristics, suspected vaccines, and AEFI description were collected. Causality and preventability were assessed using WHO and Schumock and Thornton algorithms, respectively. Logistic regression was used to estimate the reporting odds ratios of potential predictors of AEFI seriousness in children. Results: A total of 223 suspected AEFI reports were collected, and the majority of them were defined as non-serious (76.7%). Reports were mostly related to one vaccine, and to a median of two to five strains/toxoids. The total number of simultaneously administered strains/toxoids and the presence of allergens did not correlate with AEFI seriousness. Considering vaccines with a high number of administered doses (≥60,000 doses), the rates estimated for serious AEFI reports were always very low, ranging between 0.01 and 0.2/1,000 doses. Twenty-four vaccines (8,993 doses) were not related to any AEFI. Conclusion: Results of present study showed that AEFI were very rare; the vast majority of them was non-serious and, despite the claims of anti-vaccination movements, the simultaneous administration of vaccines was safe and did not influence the risk of reporting a serious AEFI, particularly in children.